Families’ Financial Stress & Well-Being: The Importance of the Economy and Economic Environments - Friedline, Terri (J Fam Econ Issues, 2020)
The Great Recession and the unfolding COVID-19 Pandemic Recession—two major disruptions to the economy that occurred just one decade apart—unequivocally confirm the importance of the economy and economic environments for understanding families’ financial stress and well-being. However, recent published literature places too little emphasis on the economy and economic environments and instead focuses on explanations rooted within individuals and families. In this article, we review research on families’ financial stress and well-being published in JFEI between 2010 and 2019, which analyzed data collected during the Great Recession and were subsequently published in the shadow of the economic downturn. We discuss the economy and economic environments as gaps in the literature and encourage future research to focus on these explanations of stress and well-being, especially in response to the pandemic recession.